Linguistic challenges of writing papers in English for scholarly publication: Perceptions of Chinese academics in science and engineering - Yihua Zhang; Hiroyuki Eto; Jianlei Cui (PLoS ONE, 2025)
This study investigates the linguistic challenges encountered by Chinese academics in science and engineering when writing for English-language scholarly publications. Employing a mixed-methods approach, the research draws on survey responses from 732 participants and insights from semi-structured interviews with 13 interviewees. Sentence construction emerged as the most significant challenge, followed by issues with vocabulary selection, cohesive devices, coherence, and grammar, with notable variation across academic ranks. Common strategies to address these challenges include utilizing online tools, seeking peer support, and employing professional editing services. The findings offer actionable recommendations for tailored academic writing training, institutional support, and the integration of advanced technological tools, aiming to enhance publication success rates among non-native English-speaking scholars.